2017
DOI: 10.1007/s00394-017-1557-1
|View full text |Cite
|
Sign up to set email alerts
|

Height and body fatness and colorectal cancer risk: an update of the WCRF–AICR systematic review of published prospective studies

Abstract: PurposeThere is no published dose–response meta-analysis on the association between height and colorectal cancer risk (CRC) by sex and anatomical sub-site. We conducted a meta-analysis of prospective studies on the association between height and CRC risk with subgroup analysis and updated evidence on the association between body fatness and CRC risk.MethodsPubMed and several other databases were searched up to November 2016. A random effects model was used to calculate dose–response summary relative risks (RR’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 92 publications
5
63
5
2
Order By: Relevance
“…A recent meta-analysis of 38 prospective cohort studies (> 71,000 cases) reported a 6% higher risk of CRC per 5 kg/ m 2 higher BMI, 2 with somewhat stronger associations in men than women and for colon than rectal cancer. 2 Despite the much lower mean BMI in China than in North America or Europe, 6 For WC and WHR, the risk estimates reported in the metaanalysis were somewhat weaker than our estimates. 2 Moreover, unlike in the present study, they differed little by sex and by anatomical site.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…A recent meta-analysis of 38 prospective cohort studies (> 71,000 cases) reported a 6% higher risk of CRC per 5 kg/ m 2 higher BMI, 2 with somewhat stronger associations in men than women and for colon than rectal cancer. 2 Despite the much lower mean BMI in China than in North America or Europe, 6 For WC and WHR, the risk estimates reported in the metaanalysis were somewhat weaker than our estimates. 2 Moreover, unlike in the present study, they differed little by sex and by anatomical site.…”
Section: Discussioncontrasting
confidence: 47%
“…2 Despite the much lower mean BMI in China than in North America or Europe, 6 For WC and WHR, the risk estimates reported in the metaanalysis were somewhat weaker than our estimates. 2 Moreover, unlike in the present study, they differed little by sex and by anatomical site. 2 Of all included studies, four studies showed that WC or WHR was more important than BMI in predicting the risk of CRC, while the converse was true for the other two studies.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Although the oncogenic mechanisms of the harmful effects of antioxidants have not been completely elucidated, it has been suggested that a high-dose intake of certain antioxidants may act as conditional pro-oxidants under high oxidative stress and exposure to lung irritants such as tobacco smoking and asbestos; and that the activity of an antioxidant is dependent on its redox potential in connection with other pro-and anti-oxidants in its microenvironment. 29,33 In a recent systematic review of blood concentrations of carotenoids and retinol, higher blood concentrations of b-carotene and retinol were inversely associated with lung cancer risk in men and not in women, 34 which illustrates the need to explore the difference between dietary intake and blood concentration. Furthermore, there are accumulating epidemiologic evidence showing gender differences in susceptibility to lung cancer.…”
Section: Discussionmentioning
confidence: 99%